Production of Crossbred Sheep in Thailand - Chaiwatanasin, Wanee; Chantsavang, Somchai; Thanintarathratharn, Bundit (Agriculture and Natural Resources, 1998)
Two hundred ninty Native - Merino crossbred lambing records of 176 ewes were analyzed. The average birth weight (kg/head), litter size (head/litter), weaning weight at 4 month (kg/head), average daily gain (gm/day), body length (cm), height (cm) and girth length (cm), were 2.62±0.04, 1.06±0.24, 18.19±3.45, 133.10±0.03, 27.14±2.78, 32.24±2.78 and 31.45±2.34 respectively. The result also indicated that maternal age significantly influenced (P<0.05) birth weight. The correlation between birth weight (BW) and body length (BL), BW and height (H), BW and girth length (GL), BL and H, BL and GL, and H and GL were 0.66, 0.66, 0.67, 0.56, 0.47 and 0.44, respectively.